PERBANDINGAN TINGKAT KINERJA KESELAMATAN DAN KESEHATAN KERJA SEBELUM DAN SESUDAH PENERAPAN OHSAS 18001 DI PT. PHAPROS, TBK. - Putri, Andhika Sekar (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2013)
Occupational health and safety (OHS) management system implementation is an effort to reduce the loss of business. Therefore, the management of PT. Phapros, Tbk. decided to obtain OHSAS 18001 certification to support its performance in OHS. This study was conducted to determine the level of compliance related to the OHS company’s performance. The collected data were analyzed using factor analysis techniques, followedby Importance Performance Analysis (IPA), and then compared with measurements prior tothe implementation of OHSAS 18001 using paired t test. The measurement result shows that there is no significant difference of the company’s performance level and the compliance level between company’s performance level and employee’s importance level compared between before and after implementation of OHSAS 18001. While there is a significant difference for employee’s importance level compared between before and after implementation of OHSAS 18001. Policies can be taken according to their priorities, such as high, medium, and low priority. One of the high priority program is to intensify trainingrelated to the employee’s OHS understanding and awareness.